ROHINGYA’S IN SEARCH FOR SECURITY: AN INTRODUCTION TO HUMAN SECURITY CONCEPT THROUGH ROHINGYA’ LENS - Riana Mardila (UIN Syarif Hidayatullah Jakarta, 2020)
Abstract. It is now 48 years from the declaration of 1982 Burma Citizenship Law. A law that legally denied the citizenship of (Muslim) Rohingya in Myanmar. It means also that for 48 years (Muslim) Rohingya remains stateless. Their fight over citizenship then becomes a global, or at least a regional challenge in International Relations sphere. In one aspect, their attempt in finding asylum to other countries at some point threaten the (arrival) state’ security. However, in another side, they also fight for their (human) security or even so (human)rights. Both securities are equally important. This article is more an introduction to the Human Security concept that was first initiated in 1994. It starts with a simple question on “how does Human Security explain the issue of Rohingya?” It seeks for key points that Human Security can explain by reflecting on Rohingya as the case study. It aims to give a bigger picture of this conflict interpreted by Human Security concept. Finally, as we are living in the globalization era, this issue is not only a state or regional challenge, but also a global challenge where IR actors can take responsibilities in helping and solving this human insecurity issue. Keywords: Rohingya; Human Security. Abstrak. Telah berlangsung 48 tahun sejak deklarasi Undang-undang Kewarganegaraan Burma 1982. Sebuah undang-undang yang secara hukum menolak kewarganegaraan (Muslim) Rohingya di Myanmar. Itu juga berarti bahwa selama 48 tahun (Muslim) Rohingya tetap tanpa kewarganegaraan. Perjuangan mereka atas kewarganegaraan kemudian menjadi tantangan global, atau setidaknya tantangan regional dalam ranah Hubungan Internasional. Di satu aspek, upaya mereka untuk mencari suaka ke negara lain pada titik tertentu mengancam keamanan (kedatangan) negara. Namun di sisi lain, mereka juga memperjuangkan keamanan (manusia) atau bahkan lebih (hak asasi manusia). Kedua sekuritas itu sama pentingnya. Artikel ini lebih merupakan pengenalan tentang konsep Keamanan Manusia yang pertama kali dimulai pada tahun 1994. Artikel ini dimulai dengan pertanyaan sederhana tentang